Reinterpretation of the Traditional Philosophy of Adat Basandi Syarak-Syarak Basandi Kitabullah in Programs and Activities Regional Government in West Sumatra - Krismena Tovalini; Yulia Hanoselina (Jurusan Ilmu Politik, FISIP, Universitas Andalas, 2022)
This article elaborates on how the community, government, traditional leaders, and religious leaders interpret the ABS-SBK philosophy when implemented in local government practice. In addition, this article also explains the need for reinterpretation of the ABS-SBK value. It explains its relationship to implementing local government programs and activities in the APBD. This article is based on qualitative research conducted in two regions, namely Padang City and Limapuluh Kota Regency. This study interviewed several informants whose backgrounds were traditional leaders, religious leaders, bureaucrats, and informal leaders in the community. This article finds that the community and traditional leaders pay little attention to that this government program must refer to the ABS-SBK philosophy. The community and traditional leaders pay attention to traditional issues in the Nagari, especially regarding the problems of Sako and Pusako. This article emphasizes the need to reinterpret the ABS-SBK philosophy, especially from meaning, value, and institutionalization.